From Refugees to Citizens: Labor Market Returns to Naturalization - Francesco Fasani; Tommaso Frattini; Maxime Pirot (Institute of Labor Economics (IZA), 2023)
Is naturalization an effective tool to boost refugees' labor market integration? We address this novel empirical question by exploring survey data from 21 European countries and leveraging variation in citizenship laws across countries, time, and migrant groups as a source of exogenous variation in the probability of naturalization. We find that obtaining citizen status allows refugees to close their gaps in labor market outcomes relative to non-refugee migrants while having non-significant effects on the latter group. We then further explore the heterogeneity of returns to citizenship in a Marginal Treatment Effect framework, showing that migrants with the lowest propensity to naturalize would benefit the most if they did. This reverse selection on gains can be explained by policy features that make it harder for more vulnerable migrant groups to obtain citizenship, suggesting that a relaxation of eligibility constraints would yield benefits for both migrants and host societies.
Keywords: J15; J61; F22; 330; forced migration; citizenship; asylum policy